The effect of transport infrastructure, congestion and reliability on mental wellbeing: a systematic review of empirical studies - Marta Conceição; Mayara Moraes Monteiro; Dena Kasraian; Pauline van den Berg; Sonja Haustein; Inês Alves; Carlos Lima Azevedo; Bruno Miranda (2022)
There has been a growing interest in understanding the interdependencies between urbanisation and mental health. Although transportation in cities is complex and of foremost importance to support the mobility of goods and passengers, little is known about how it relates to individual psychological distress. This review aims to provide an up-to-date synthesis of research evidence about the influence of transport infrastructure and operational performance (congestion, delays and reliability) on mental health/wellbeing. It is structured around three main interacting concepts that determined the search/selection of articles: identification of the above-mentioned transport-related exposures; use of psychological and physiological validated instruments; and the outcome on mental health/wellbeing. Ultimately, 69 studies were identified involving an empirical quantitative focus that met the inclusion criteria. We summarise the instruments most reported in these studies and the findings linking transport indicators and psychological and physiological outcomes. Across the review, we identified evidence of the contribution of key transport infrastructure, congestion and delay indicators on negative affective states and psychophysiological distress. Regarding transport reliability, the scarce number of studies identified did not allow for drawing similar firm conclusions. We conclude by discussing some limitations and providing recommendations for future research and policy-making agendas.